Validación de diferentes opciones de manejo para el control de la roya del café (Hemileia vastatrix B Br.) en la finca Santa Ana, El Mombacho, Nicaragua - Sánchez Ñurinda, M.A.; Morales Gutiérrez, C.; Monterroso Salvatierra, D. Asesor; Blanco Navarro, M.A. Asesor; Mendoza Garcia, M. Consultor (Managua (Nicaragua), 1996)
Sumario (Es)
Ilus.; 51 ref.
Tesis (Ing Agr)
Keywords: COFFEA ARABICA; CONTROL DE ENFERMEDADES; ROYA; HEMILEIA VASTATRIX; ANTRACNOSIS; NICARAGUA; MOMBACHO